2006
DOI: 10.1159/000097392
|View full text |Cite
|
Sign up to set email alerts
|

Human Coronavirus Infection among Children with Acute Lower Respiratory Tract Infection in Thailand

Abstract: Objective: This study was performed to further identify the previously uncharacterized human coronavirus 229E (hCoV-229E) and human coronavirus OC43 (hCoV-OC43) in Thailand by using the RT-PCR technique. In addition, we performed this study in order to delineate the prevalence, the potential clinical impacts and evaluation of the genetic characterization of this pathogen in young children who presented with acute lower respiratory tract infections (ALRI). Methods: We obtained nasopharyngeal secretions (NPs) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…Despite sensitive assays, we found the prevalence of infection with HCoVs to be very low during the study period. Similar to our findings, a recent study from Bangkok, Thailand, conducted during 2002-2003 found 229E and OC43 infections in 4.9% of young children with acute respiratory tract illness; however, the majority were 229E infections rather than OC43 infections [44]. The proportion of HCoV types we detected is similar to those of other international studies reporting HCoVs from both upper and lower acute respiratory tract illness by use of PCR assays [12-16, 18, 20-23, 31, 45].…”
Section: Discussionsupporting
confidence: 91%
“…Despite sensitive assays, we found the prevalence of infection with HCoVs to be very low during the study period. Similar to our findings, a recent study from Bangkok, Thailand, conducted during 2002-2003 found 229E and OC43 infections in 4.9% of young children with acute respiratory tract illness; however, the majority were 229E infections rather than OC43 infections [44]. The proportion of HCoV types we detected is similar to those of other international studies reporting HCoVs from both upper and lower acute respiratory tract illness by use of PCR assays [12-16, 18, 20-23, 31, 45].…”
Section: Discussionsupporting
confidence: 91%
“…According to our previous observation, the prevalence of HCoVs infection in children who had acute LRT diseases in Thailand was found to be extremely low. 27 HRV was the most common respiratory pathogen found in 87 samples from 84 patients indicating a prevalence of 30% in this sample population. Two patients had a total of 5 HRV infections between them.…”
Section: Resultsmentioning
confidence: 81%
“…Our data clearly support the hypothesis that HboV plays a significant role as etiological cause of bronchiolitis in children. However, it is possible that we underestimated the prevalence of infections by other common respiratory viruses because PCR was not applied to all possible respiratory pathogens, especially parainfluenza 4a and 4b, and coronaviruses OC43, 229E, NL64 and HKU1), which are considered minor causes of childhood bronchiolitis (Kaplan et al, 2008;Theamboonlers et al, 2007;Vabret et al, 2008). Moreover, we did not test respiratory samples from a control group of children matched for age, residence area and month of hospitalization and who were free of known respiratory symptoms or diseases.…”
Section: Discussionmentioning
confidence: 99%